A lesson in motion stays in motion: If students lead, will teachers follow?. (December 2022) - Miller, Samuel; Stallings, Sarah; Massey, Dixie; Metzger, Salem R.
While endorsed as critical for promoting learning, students' interest in a topic has had minimal, if any, influence on curriculum development. Teachers thus are challenged to promote students' interest within an established curriculum. After students demonstrated misunderstandings after reading an article about bacteria, Sarah Stallings and Samuel Miller, a 4th-grade teacher and university researcher, decided to base their instruction on students' queries and concerns. This one lesson provided the impetus for a series of activities across the school year that allowed students to become more actively involved in choosing what they would learn and how they would learn it. What students viewed as important and interesting determined the nature and format of their daily studies .